Omalizumab in combination with subcutaneous immunotherapy for the treatment of multiple allergies associated with attention-deficit/hyperactivity disorder: a case report and a literature review - Ding, Bo; Lu, Yanming (Frontiers in Pharmacology, 2024)
We describe a case of a 10-year-old boy with asthma (AS), accompanied by allergic rhinitis (AR), food allergy (FA), and combined Attention Deficit/Hyperactivity Disorder (ADHD), who was treated in Shanghai Renji Hospital on 11 July 2020. The efficiency of the previous treatment with salmeterol/ticlosone was poor. Treatment with montelukast sodium resulted in the development of neurological symptoms. Treatment with omalizumab in combination with subcutaneous immunotherapy (SCIT) was then initiated in our department based on anti-asthmatic therapy. Symptoms of asthma were completely controlled, and FA and AR symptoms improved. The treatment regimen led to a significant improvement in ADHD symptoms and the overall quality of life of the patient. The literature search was done in the PubMed database using “attention deficit/ hyperactivity disorder/ADHD” and “asthma” as keywords and identified 47 relevant articles. In conclusion, our results show that treating asthma with omalizumab in combination with salmeterol/ticlosone and SCIT is efficient in controlling symptoms of multiple allergies and may lead to the improvement in ADHD and the overall quality of life of pediatric patients with ADHD. While current studies suggest that allergic diseases are closely related to ADHD, there is still a lack of studies or case reports of complete treatment protocols to provide clinical clues for the management of the disease.